Analyzing and estimating portfolio performance of Bangladesh stock market - Hasan, Md. Zobaer; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (Science Publication, 2013)
Capital Asset Pricing Model (CAPM) is one of the most important developments in the finance literature. Simply, CAPM is a model that describes the relationship between risk and expected return. The theoretical validity of CAPM is well tested and accepted but the practical validity of CAPM is in questioned.This study is designed to analyze and estimate the portfolio performance of Bangladesh stock market in a CAPM framework.For this study, monthly stock returns from 80 companies for the period of January 2005 to December 2009 are chosen.In order to examine whether the CAPM is satisfied in the portfolio or not, the 80 stocks are arranged in descending order of beta and 10 portfolios are being made of eight stocks in each.The All Share Price Index (DSI) is used as a proxy for the market portfolio and Bangladesh government 3-Month T-bill rate is used as the proxy for the risk-free asset. The results of this analysis show that the intercept terms are not significantly different from zero, linearity in the securities market line and insignificant unique risk for the 10 portfolios during the period. But, the results in term of slope contradict the CAPM hypothesis and indicate evidence against the CAPM in the portfolios.This analysis will obviously be used as a basis of reference for future investigates and the researchers and they will get proper instruction from this study.